Assessing the individual relationships between physical test improvements and external load match parameters in male professional football players—a brief report - Byrkjedal, Per Thomas; Bjørnsen, Thomas; Luteberget, Live Steinnes; Ivarsson, Andreas; Spencer, Matt (Frontiers in Sports and Active Living, 2024)
Purpose This study aimed to explore whether a meaningful improvement in physical performance following an in-season strength training intervention can be related to external load match parameters at an individual level in professional male football players. Methods Eight male professional football players (25.4 ± 3.1 years, 184.1 ± 3.4 cm, 79.3 ± 2.2 kg) completed a 10-week strength intervention period in addition to football-specific training and matches. Commonly used physical and external load measures were assessed before and after intervention. Physical performance improvements had to exceed the measurement’s typical error and the smallest worthwhile difference (SWD) to be considered meaningful. External load match parameters were assessed before and after the intervention period using SWD and non-overlap of all pairs (NAP) analysis. A Bayesian pairwise correlation analysis was performed to evaluate relationships between changes in physical performance and external load match parameters. Results Three players displayed meaningful improvements in two to five physical performance measures. However, positive changes exceeding the SWD and positive effects in NAP results were observed for all players in external load match parameters. Kendall's tau correlation analysis showed evidence (base factor >3) for only one correlation (maximum speed − decelerations, τ = −0.62) between the changes in physical performance and external load measures, while the remaining comparisons exhibited no relation. Conclusions The findings suggest that improvements in physical performance may not necessarily translate to improvements in external load match parameters. Further research, with larger sample sizes, is needed to understand potential mechanisms between acute and chronic physical performance changes and football external load parameters during training and matches.